Effect of Potassium Permanganate on Physico-Chemical Changes and Shelf Life of Mango (Mangifera indica L.) - Azad, M Ittefaqul; Mortuza, M Golam; Nahar, N Ahktar; Huq, Shamina; Alam, M Ashraful (The Agriculturists, 2010)
Mango fruits (cv. Fazli and Khirsapat) were treated with 3 dosages (5, 10 and 20g) of Potassium permanganate (PP) and kept in sealed polythene bags at normal room temperature (28-33 °C). It was observed that PP had little effect on colour development in both the cultivars. All the treated fruits remained green upto 6 days of storage. All the treatments delayed ripening of mango fruits from 2.37 to 4.84 days as compared with untreated control. Fruits treated with 5g PP required longer time for ripening followed by 10 and 20g. The results indicated that PP had no effect on weight loss and was not able to improve appearance or eating quality of the fruits. Mango fruits stored in polyethylene bag showed lower TSS and sugar contents and subsequently possessed lower ratings for eating quality which cause less sweet and slightly bitter taste. The longest shelf life was noted in fruits treated with 20g followed by 10g and 5g PP although there were no significant differences among the treatments.